Online Food and Beverage Ordering System Based On Web-Based Makanman Restaurant: Sistem Pemesanan Makanan dan Minuman Online Berbasis Web Restoran Makanman - Elfina Novalia; Abdul Hafiz; Agustia Hananto (SYSTEMATICS, 2022)
The development of information systems to date continues to increase and rapidly, with the development of more advanced technology so that information can be accessed quickly, precisely, anytime and anywhere. Makanman is one of the SMEs located on Jl. Ronggo Waluyo Teluk Jambe Timur Karawang, Makanman is a business that is engaged in providing ready-to-eat food and drinks, with the current condition of placing orders directly to the cashier, causing an ineffective queue for ordering, therefore this information system is very assist in the ordering process at Makanman. The end result of this food ordering system is expected to provide convenience and comfort in ordering food and speed in the ordering process so there is no need to queue anymore.